Petrography, geochemistry, age, and stratigraphic significance of the Mississippian Boyd Creek tuff, southern New Brunswick, Canada - Park, Adrian F.; Hinds, Steven J.; McFarlane, Christopher R.M.; Boucher, Brandan; Stimson, Matthew R.; Clark, Perry (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2024)
The Boyd Creek tuff consists of two pyroclastic flow deposits and more widespread air-fall tuff within a Mississippian red bed sequence located in outcrop and boreholes around Weldon and Pre d’en Haut, Albert and Westmorland counties, New Brunswick. Long recognized as an important stratigraphic marker, it has been placed in either the Tournaisian Weldon Formation or Visean Hillsborough Formation by previous workers, with a position in the upper Tournaisian Weldon Formation being the most recent interpretation. A Visean laser ablation-inductively coupled plasma-mass spectrometry U–Pb zircon age of 336.9 ± 2.0 Ma is consistent with the interpretation that the tuff is part of the Windsor Group and within a fine-grained red and grey sequence of the Hillsborough Formation. Although the tuff is altered and contains abundant xenoliths and xenocrysts, petrography and chemistry are consistent with rhyolite or dacite composition. Its composition and age suggest that the Boyd Creek tuff is one of several volcanic units interpreted to be in the Windsor Group or its temporal equivalents, including rhyolite-trachyte lavas of Cumberland Hill (Cumberland Hill Formation, Mabou Group), tuff in carbonate-evaporite sequence at the Picadilly Mine (Penobsquis), and the red bed Shin Formation (Mabou Group) at Hurley Creek near Minto. Locating and dating other ‘ash beds’ in the Windsor Group offers a way to resolve long-standing issues of correlation in the Visean of New Brunswick and Nova Scotia.